Pengaruh Motivasi Kerja terhadap Peningkatan Kinerja Karyawan: Studi Kasus pada Unit Rekanan Koperasi Konsumen Mulia di RSUD Majalaya - Dadan Hamdani; Dina Dwijayanti (LPPM Universitas Koperasi Indonesia, 2025)
This study aims to analyse the impact of work motivation on employee performance at the Consumer Cooperative Mulia Unit in RSUD Majalaya. Work motivation is recognized as a crucial factor influencing individual productivity and organizational success. A quantitative research methodology was employed, utilizing a questionnaire distributed to 30 respondents, including employees and managers. The collected data were analysed using descriptive and inferential statistical techniques to identify the relationship between work motivation and employee performance. The findings indicate a significant positive relationship between work motivation and employee performance, where factors such as recognition, job satisfaction, job challenges, and support from supervisors play a substantial role in enhancing performance. Employees who feel motivated tend to demonstrate better performance, including achieving targets and completing tasks on time. These results have important implications for the management of Koperasi Konsumen Mulia in designing more effective human resource management strategies. By improving various aspects of work motivation, it is expected that employee performance can be enhanced, ultimately leading to positive outcomes for the organization as a whole. This research recommends the implementation of ongoing training and development programs to further boost work motivation among employees.